Twelve tips for novice academic staff supporting medical students in distress. (3rd July 2021) - Hodgson, Jessica C.; Bretherton, Roger
Abstract: The importance of having university systems to support students' wellbeing and welfare needs has been well documented, with an increasing literature on best practice for structuring student support services from an institutional perspective. Nevertheless, individual members of academic staff are often required to deal with students who are experiencing challenging circumstances, and this is especially so in the pre-clinical phases of medical training. The prospect of advising and supporting students who are in difficulty and who may be distressed, can be daunting and can also negatively impact the wellbeing of the staff involved. These tips present the practical guidelines we have developed on how academic staff can best manage meetings with students in situations of crisis or high emotion.